EXISTENCE OF SOLUTIONS FOR IMPULSIVE ANTI-PERIODIC BOUNDARY VALUE PROBLEMS OF FRACTIONAL ORDER - Ahmad, Bashir; Nieto, Juan J. (Taiwanese journal of mathematics, 2011)
In this paper, we prove the existence of solutions for impulsive differential equations of fractional orderq∈ (1, 2] with anti-periodic boundary conditions in a Banach space. Our study is based on the contraction mapping principle and Krasnoselskii's fixed point theorem. 2000Mathematics Subject Classification: 34A34, 34B15. Key words and phrases: Fractional differential equations, Impulse, Anti-periodic boundary conditions, Existence, Fixed point theorem.